Hazardous effect of raw sewage disposal from indigenous housing settlement on natural water bodies - Nasrolah, Navid; Ibrahim, Rahinah; Mohammad, Thamer Ahmed; Idris, Azni (Excellent Publishers, 2014)
One of the problems that are causing a threat to public health is a sanitation system of indigenous houses built on water. The traditional way of life of indigenous society living in housing settlements over rivers or the sea is becoming a source of environmental pollution. These houses did not actually have a proper sanitation system for disposing wastes from toilets. The sanitation systems for these houses unfortunately dispose wastes directly into natural water bodies. The centralization of the waste disposal may cause problem to the public due to technical and financial different faced by the authorities. This research requires gathering relevant data source based on direct observation and indirect observations. Also this project will utilize on qualitative data collection tools, but is rooted in a qualitative epistemological position that recognizes the importance of locating the research within a particular social, cultural, and house settlement. This paper surveys the literature on problems that arise from raw sewerage disposed into natural water bodies before any sanitation is proposal to solve the problem. Also the potential solutions to the problem were discussed too.